2012
DOI: 10.1246/bcsj.20120167
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Quadrupole Contributions from Interface and Bulk in Second-Order Optical Processes

Abstract: A unified treatment of the dipole and quadrupole contributions to the second-order optical response is developed. The concept of the effective susceptibility is expanded to incorporate both the surface and bulk contributions. This treatment allows us to quantitatively evaluate both surface and bulk contributions in experimental SFG/SHG spectra. The present theory clarifies a number of qualitative features in the quadrupole contribution, and is thereby utilized to settle recent confusions about the quadrupole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…It has been theoretically shown that a bulk quadrupolar contribution can be distinguished from an interfacial contribution by varying the optical geometry of the experiment. 39 This will be the subject of future study.…”
mentioning
confidence: 95%
“…It has been theoretically shown that a bulk quadrupolar contribution can be distinguished from an interfacial contribution by varying the optical geometry of the experiment. 39 This will be the subject of future study.…”
mentioning
confidence: 95%
“…Recently, Shiratori and Morita [12] proposed a computational framework for the evaluation of SFG spectra, using mixed quantum and molecular mechanics methods to compute dipole and quadrupole contributions from molecular non-linear polarizabilities. However their method was applied only to a non-polar molecular liquid [13], using empirical atomic potentials.…”
mentioning
confidence: 99%
“…The latter are of key importance to account for the variation of the electric field across the interface. [9,12], where χ IQB eff is fully determined by bulk properties and can be computed using a bulk sample (with x,y,z periodicity); χ IQI eff is instead computed using a slab geometry [25]. The χ BQ term [27] can be experimentally identified by comparing signals from transmission or reflectance optical geometries [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations